COVID Stress Scales (CSS): Psychometric Evidence in the Brazilian Context - Silva Brito, Rislay Carolinne (2022)
Objective. Adapt the COVID Stress Scales (CSS), gathering psychometric evidence, and to verify the pattern of relationship with anxiety compared to COVID-19. Method. Two studies were carried out with participants from different Brazilian states. In the first (n = 423) the exploratory factor analysis suggested a pentafactorial structure. In the second (n = 300), a confirmatory factor analysis was performed, testing a pentafactorial model. Evidence of convergent and discriminant validity was gathered. Pearson’s correlation (r) was performed, which showed positive and statistically significant relationships between anxiety and stress in the face of COVID, indicating validity based on external measure. Results. Satisfactory internal consistency was found in both studies. It is concluded that the CSS is valid and reliable and can assist in the assessment of individuals with stress caused by the COVID pandemic and its correlated factors.